Aortic insufficiency in the patient on contemporary durable left ventricular assist device support: a state-of-the-art review on preoperative and postoperative assessment and management - Saeed, Diyar; Grinstein, Jonathan; Kremer, Jamila; Cowger, Jennifer A. (The journal of heart and lung transplantation, 2024)
The development of aortic insufficiency (AI) during HeartMate 3 durable left ventricular assist device (dLVAD) support can lead to ineffective pump output and recurrent heart failure symptoms. Progression of AI often comingles with the occurrence of other hemodynamic-related events encountered during LVAD support, including right heart failure, arrhythmias, and cardiorenal syndrome. While data on AI burdens and clinical impact are still insufficient in patients on HeartMate 3 support, moderate or worse AI occurs in approximately 8% of patients by 1 year and studies suggest AI continues to progress over time and is associated with increased frequency of right heart failure. The first line intervention for AI management is prevention, undertaking surgical intervention on the insufficient valve at the time of dLVAD implant and avoiding excessive device flows and hypertension during long-term support. Device speed augmentation may then be undertaken to try and overcome the insufficient lesion, but the progression of AI should be anticipated over the long term. Surgical or transcatheter aortic valve interventions may be considered in dLVAD patients with significant persistent AI despite medical management, but neither intervention is without risk. It is imperative that future studies of dLVAD support capture AI in clinical end-points using uniform assessment and grading of AI severity by individuals trained in AI assessment during dLVAD support.
Version des Artikels: 25. Oktober 2024
Gesehen am 12.05.2025